The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1167/iovs.08-2384
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Deposition and Functional Impairment in the Retina of the APPswe/PS1ΔE9 Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Purpose To determine whether β-amyloid (Aβ) deposition affects the structure and function of the retina of the APPswe/PS1ΔE9 transgenic (tg) mouse model of Alzheimer’s disease. Methods Retinas from 12–19 month-old APPswe/PS1ΔE9 tg and age-matched non-transgenic (ntg) littermates were single or double stained with thioflavine-S and antibodies against Aβ, glial fibrilar acidic protein (GFAP), microglial marker F4/80, choline acetyltransferase (ChAT) and syntaxin 1. Quantification of thioflavine-S positive plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
181
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(211 citation statements)
references
References 58 publications
25
181
1
4
Order By: Relevance
“…68 Furthermore, AB plaques, hyperphosphorylated tau, and retinal microvascular neuro-inflammation have been identified in the retinas of AD transgenic mice. 69,70 The main ocular biomarker investigated for AD has been thinning of the RNFL, as this may reflect both generalised neurodegeneration and local involvement, and this is reviewed below. Other ocular biomarkers investigated in AD include pupillary abnormalities: hypersensitivity to pupillary dilatation with cholinergic antagonist eye drops, [71][72][73] supersensitive pupillary response to cholinergic agonists, 74 and altered pupil flash responses.…”
Section: The Eye In Admentioning
confidence: 99%
See 1 more Smart Citation
“…68 Furthermore, AB plaques, hyperphosphorylated tau, and retinal microvascular neuro-inflammation have been identified in the retinas of AD transgenic mice. 69,70 The main ocular biomarker investigated for AD has been thinning of the RNFL, as this may reflect both generalised neurodegeneration and local involvement, and this is reviewed below. Other ocular biomarkers investigated in AD include pupillary abnormalities: hypersensitivity to pupillary dilatation with cholinergic antagonist eye drops, [71][72][73] supersensitive pupillary response to cholinergic agonists, 74 and altered pupil flash responses.…”
Section: The Eye In Admentioning
confidence: 99%
“…101 Other studies of human tau transgenic mice 79 have reported accumulations of hyperphosphorylated transgenic tau in the RNFL and RGCs. Other transgenic mice models have suggested that the inner plexiform layer may be a more sensitive biomarker for detecting AD-related changes compared with RGCs, 70,80 making it difficult to draw firm conclusions. 102 However, both human and mouse studies suggest that AD-related pathology is seen in the retina.…”
Section: The Ganglion Cell Layer In Admentioning
confidence: 99%
“…Plaques and tangles have not been found in the human retina although Aβ has been isolated in aged human retinas [132]. Research on the retinas of AD transgenic mice has demonstrated Aβ plaques, hyperphosphorylated tau, increased microvascular deposition of Aβ and neuroinflammation [133][134]. Aβ immunotherapy in such transgenic mice has resulted in the clearance of retinal plaques but an increase in retinal amyloid angiopathy, identifying non-invasive retinal imaging as an alternative method for monitoring disease response to immunotherapy in these mice.…”
Section: (Figure 4)mentioning
confidence: 99%
“…Perez et al (5) found retinal Aβ plaques in the APPswe/PS1∆E9 transgenic mouse at the age of 12 -13 months associated with a significant increase in microglial activity. In the brain of these mice, Aβ plaques were found at the age of 2 -6 months.…”
Section: Animal Modelsmentioning
confidence: 99%